Modelling of ‘satellite-to-aircraft’ link for self-separation - Kharchenko, Volodymir; Barabanov, Yurii; Grekhov, Andrii (Transport, 2013)
The aim of this paper is to design the original model of communication channel ‘Satellite-to-Aircraft’ for self-separation with error-control coding using MATLAB Simulink software. Studying the signal transmission through a communication channel without coding and with convolutional coding the following parameters were changed: losses in a free space from 0 dB to 225 dB; noise temperature of an aircraft receiver 20 K and 290 K; simultaneous changing of antennas diameter; phase offsets from 0° to 20°; nonlinearity of satellite high power amplifier; satellite phase noise; and a data bit rate. BER is vanishing for free space path losses changing from 0 dB to 221 dB at the use of convolutional coding and a noise temperature 20 K, for diameters of all antennas of more than 1.2 m, and at phase shifts up to 4°. The signal constellation shows a presence of strong distortions during signal transmission. The proposed model can be used as a basic model for investigation of communication between two unmanned aircraft systems. First Published Online: 24 Dec 2013